The representation of "South Africanness" in the locally produced television production, Generations - Dentlinger, Lindsay (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2000)
The aim of this study is to analyse selected episodes of the locally produced television programme Generations, in order to identify specific ways in which the programme seeks to forge a South African identity, and in so doing, 'flag' our nationhood as South Africans. These elements of 'South Africanness' are broadly defined as connections to a South African way of life, context, values and experiences. Generations is a programme produced under South African broadcasting local content provisions. These provisions arise out of the need, inter alia, to reflect the identity and multi-cultural nature of South Africa in order to foster 'national identity' and 'national culture'. These elements of 'South Africanness' are extracted through a genre and ideological analysis of selected sample episodes, taking into consideration the theoretical frameworks of the politics of representation and identity. The production context of, and representations made, in Generations, are found to be situated largely within the context of the South African discourses of the 'rainbow nation', 'African renaissance' and 'black economic empowerment'. The analysis concludes that through the various categories of representations of 'South Africanness' in the selected episodes of Generations, specific instances of identity, that of national culture and national identity are formed.
Keywords: Television soap operas -- South Africa; National characteristics, -- South African, In Literature